Optimizing Vehicle Loading To Improve Operational Safety At Kmp. Dharma Ferry VIII - I Made Agustine Wikana Putra; Bustamin Bustamin; Diah Vitaloka Hartati (CV. AFDIFAL MAJU BERKAH, 2026)
Sea transportation by Roll-on/Roll-off (Ro-Ro) vessels requires the implementation of vehicle lashing according to standards to prevent cargo shifting and maintain the operational safety of the vessel. Observations at KMP Dharma Ferry VIII showed that there were still problems in the form of cargo density, inadequate lashing equipment conditions, limited loading and unloading time, and inconsistent implementation of procedures. This study aims to analyze the implementation of vehicle load lashing and the factors that influence its effectiveness. The study used a qualitative descriptive approach with a purposive sampling technique. The study population was all crew members involved in loading and lashing activities, while the sample consisted of Chief Officers, Bosuns, Helmsmen, and Classes. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using data reduction, data presentation, conclusion drawing, Fishbone diagrams, and NVivo Project Map visualization. The results showed that the effectiveness of lashing was influenced by the condition of lashing equipment, consistency of procedure implementation, limited loading and unloading time, and human factors in the form of crew fatigue. It was concluded that improving operational safety requires regular maintenance of lashing equipment, consistent implementation of SOPs, more effective supervision, and optimal management of working time and crew adequacy.